Epigenetic silencing of SALL2 confers tamoxifen resistance in breast cancer. Issue 12 (28th October 2019) - Ye, Liping; Lin, Chuyong; Wang, Xi; Li, Qiji; Li, Yue; Wang, Meng; Zhao, Zekun; Wu, Xianqiu; Shi, Dongni; Xiao, Yunyun; Ren, Liangliang; Jian, Yunting; et al.
Abstract: Resistance to tamoxifen is a clinically major challenge in breast cancer treatment. Although downregulation of estrogen receptor‐alpha (ERα) is the dominant mechanism of tamoxifen resistance, the reason for ERα decrease during tamoxifen therapy remains elusive. Herein, we reported that Spalt‐like transcription factor 2 (SALL2) expression was significantly reduced during tamoxifen therapy through transcription profiling analysis of 9 paired primary pre‐tamoxifen‐treated and relapsed tamoxifen‐resistant breast cancer tissues. SALL2 transcriptionally upregulated ESR1 and PTEN through directly binding to the DNA promoters. By contrast, silencing SALL2 induced downregulation of ERα and PTEN and activated the Akt/mTOR signaling, resulting in estrogen‐independent growth and tamoxifen resistance in ERα‐positive breast cancer. Furthermore, hypermethylation of SALL2 promoter was found in tamoxifen‐resistant breast cancer. Importantly, in vivo experiments showed that DNA methyltransferase inhibitor‐mediated SALL2 restoration resensitized tamoxifen‐resistant breast cancer to tamoxifen therapy. These findings shed light on the mechanism of SALL2 in regulation of ER and represent a potential clinical signature that can be used to categorize breast cancer patients who may benefit from co‐therapy with tamoxifen and DNMT inhibitor. Synopsis: Resistance to tamoxifen is a clinically important challenge for breast cancer treatment. This study uncovers a mechanism by which the transcription factor SALL2 regulates ERα, and identifies a subset of breast cancer patients who might benefit from tamoxifen/DNMTs inhibitor co‐therapy. ALL2 hypermethylation status was correlated with poorer clinical outcomes in breast cancer patients receiving tamoxifen therapy. Promoter methylation‐mediated SALL2 silencing conferred tamoxifen resistance and estrogen‐independent cell growth in breast cancer. Loss of SALL2 transcriptionally downregulated both ESR1 and PTEN, resulting in inhibition of Erα activity and activation of PI3K/Akt signaling. Restoration of SALL2 using DNMT inhibitor 5‐Aza‐dC re‐sensitized a subset of breast cancer to tamoxifen therapy in vivo . Abstract : Resistance to tamoxifen is a clinically important challenge for breast cancer treatment. This study uncovers a mechanism by which the transcription factor SALL2 regulates ERα, and identifies a subset of breast cancer patients who might benefit from tamoxifen/DNMTs inhibitor co‐therapy.